Students Perception on the Effectiveness of Online Teaching - Leeja Bonny Thomas1 , Merlin Suji2 , Poonam Yadav1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
With the prevalence of online teaching, it’s vital to convey student’s quality education. Institutes are utilizingonline teaching to extend effectiveness furthermore as accessibility of learning throughout this pandemic.Online teaching may be a great platform that provides learners to realize skills and strengthen their knowledgeat their own place. [1]As teachers and support systems to students we would like to provide services which are beneficial as wellas useful for the learners and that capture their interest towards online learning. So, to do so it’s important tounderstand students perception regarding online teaching that will lead to student’s satisfaction. [2]The result shows that 73 % of students remained neutral towards satisfaction on instructional design anddelivery of a course compared to classroom teaching, 53% of students believe on the importance of theirroles and responsibilities to own a positive expertise with an online class and 76% of students agree thatteachers and support systems is effective in providing services as required.